α-Mangostin Inhibited M1 Polarization of Macrophages/Monocytes in Antigen-Induced Arthritis Mice by Up-Regulating Silent Information Regulator 1 and Peroxisome Proliferators-Activated Receptor γ Simultaneously - Wu YJ; Zhang SS; Yin Q; Lei M; Wang QH; Chen WG; Luo TT; Zhou P; Ji CL (Dove Medical Press, 2023)
Yi-Jin Wu,1- 3,* Sa-Sa Zhang,1,* Qin Yin,1 Ming Lei,2 Qi-Hai Wang,4 Wen-Gang Chen,1 Ting-Ting Luo,1 Peng Zhou,5 Cong-Lan Ji4,6 1Department of Pharmacy, The Second Affiliated Hospital of Wannan Medical College, Wuhu, 241000, People's Republic of China; 2Xin'an Medical Research Center, The First Affiliated Hospital of Wannan Medical College, Wuhu, 241000, People's Republic of China; 3Vascular Diseases Research Center of Wannan Medical College, Wuhu, 241000, People's Republic of China; 4School of Pharmacy, Anhui College of Traditional Chinese Medicine, Wuhu, Anhui, 241000, People's Republic of China; 5School of Integrated Chinese and Western Medicine, Anhui University of Chinese Medicine, Hefei, 230000, People's Republic of China; 6Research Center of Integration of Traditional Chinese and Western Medicine, Wannan Medical College, Wuhu, 241000, People's Republic of China*These authors contributed equally to this workCorrespondence: Peng Zhou; Cong-Lan Ji, Email zhoupeng@ahtcm.edu.cn; 37709103@qq.comBackground: α-Mangostin (MG) showed the potentials in alleviating experimental arthritis, inhibiting inflammatory polarization of macrophages/monocytes, and regulating peroxisome proliferators-activated receptor γ (PPAR-γ) and silent information regulator 1 (SIRT1) signals. The aim of this study was to analyze the correlations among the above-mentioned properties.Methods: Antigen-induced arthritis (AIA) was established in mouse, which was treated with MG in combination with SIRT1/PPAR-γ inhibitors to clarify the role of the two signals in the anti-arthritic actions. Pathological changes were systematically investigated. Phenotypes of cells were investigated by flow cytometry. Expression and co-localization of SIRT1 and PPAR-γ proteins in joint tissues were observed by the immunofluorescence method. Finally, clinical implications from the synchronous up-regulation of SIRT1 and PPAR-γ were validated by experiments in vitro.Results: SIRT1 and PPAR-γ inhibitors (nicotinamide and T0070097) reduced the therapeutic effects of MG on AIA mice, and abrogated MG-induced up-regulation of SIRT1/PPAR-γ and inhibition of M1 polarization in macrophages/monocytes. MG has a good binding affinity to PPAR-γ, and MG promoted the co-expression of SIRT1 and PPAR-γ in joints. Synchronously activating SIRT1 and PPAR-γ was revealed to be necessary by MG to repress inflammatory responses in THP-1 monocytes.Conclusion: MG binds PPAR-γ and excites this signaling to initiate ligand-dependent anti-inflammatory activity. Due to certain unspecified signal transduction crosstalk mechanism, it then promoted SIRT1 expression and further limited inflammatory polarization of macrophages/monocytes in AIA mice.Graphical Abstract: Keywords: rheumatoid arthritis, mangosteen, metabolism, inflammation, immune